Cutaneous manifestations of COVID-19: a case report and review of the literature - Martinez Arismendi, Jose Luis; Zepeda Torres, Jose Maria; Osuna Gutierrez, Felix; Fischert Melendez, Laura; Gutiérrez García, Grecia Jazmín; Padilla, Paola Lizette (International Journal of Research in Dermatology, 2022)
Since the onset of the SARS-Cov2 pandemic, new data and peculiarities have emerged within the range of manifestations caused by this virus. Multisystem inflammatory syndrome in children (MIS-C) affects a small percentage of pediatric patients infected with SARS CoV 2 and characterized by fever, lab evidence of inflammation, multisystem involvement, and severe illness requiring hospitalization. Cutaneous findings are often present in these patients and are notable for their heterogeneity and poor characterization. We present case of pediatric patient with COVID-19 and cutaneous manifestations consistent with a multisystem inflammatory syndrome.